Who said as the first? Morphological determinants of the human speech - Kujawa, Betina (Anthropological Review, 1995)
The evolution of human speech was probably involved into development of brain structures responsible for cultural behaviour, specially tool-making. Moreover, it has been sugested that only Homo erectus species had the speech apparatus formed the way which allowed to articulate some sounds.